Corporate responsibility for wealth creation and human rights - Enderle, Georges (Cambridge : Cambridge University Press, 2021)
Georges Enderle proposes a radically new understanding of corporate responsibility in the global and pluralistic context. This book introduces a framework that integrates the ideas of wealth creation and human rights, which is illustrated by multiple corporate examples, and provides a sharp critique of the maximizing shareholder value ideology. By defining the purpose of business enterprises as creating wealth in a comprehensive sense, encompassing natural, economic, human and social capital while respecting human rights, Enderle draws attention to the fundamental importance of public wealth, without which private wealth cannot be created. This framework further identifies the limitations of the market institution and self-regarding motivations by demonstrating that the creation of public wealth requires collective actors and other-regarding motivations. In line with the UN's Guiding Principles on Business and Human Rights, this book provides clear ethical guidance for businesses around the world and a strong voice against human right violations, especially in repressive and authoritarian regimes and populist and discriminatory environments.
Title from publisher's bibliographic system (viewed on 11 Jan 2021).
Keywords: Social responsibility of business; Wealth -- Moral and ethical aspects; Globalization -- Moral and ethical aspects; Human rights